Modern Principles of Oral Rehydration Therapy in Treatment of Acute Enteric Infections In Children - A.Ye. Abaturov; O.N. Gerasimenko; I.L. Vysochina; Ye.L. Krivusha; O.A. Yermolaeva; I.A. Girina (Zaslavsky O.Yu., 2012)
The paper deals with basic principles of oral rehydration therapy in children with infectious diarrhea, which occur with the development of exsicosis. It was emphasized that prescription of oral rehydration therapy promotes more rapid recovery of children and prevents adverse outcomes.